Fix it, nitrogen! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Nitrogen fixation in tropical cropping systems. 2nd edition By K E Giller, CABI Publishing, 2001. 425 pp. ISBN 0 85199 417 2 GBP 60 Euro 97.10